2021
DOI: 10.3906/sag-2007-145
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing anterior/low anterior resection syndrome after rectal or sigmoid resections

Abstract: Background/aim: Sphincter preserving surgery is one of the main goals in the treatment of rectal cancer because it improves the quality of life (QoL). However, some patients may experience disrupted symptoms called anterior or low anterior resection syndrome (LARS). This study designed to evaluate the frequency and influencing factors of LARS in patients who had undergone sigmoid or rectal resection. Materials and methods: In this retrospective, clinical study, patients who had undergone rectal or sigmoid rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
2
8
0
1
Order By: Relevance
“…These studies agree that major LARS is associated with a decreased HRQoL [14,15,31,32]. However, also, patient and treatment characteristics (e.g., age, radiotherapy, low anastomosis) of patients that develop major LARS are likely to influence HRQoL [31,33]. In this study, patients with major LARS had significantly more complaints of embarrassment than patients with a stoma, which can be an important issue to discuss with a patient when a high risk of major LARS is anticipated.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…These studies agree that major LARS is associated with a decreased HRQoL [14,15,31,32]. However, also, patient and treatment characteristics (e.g., age, radiotherapy, low anastomosis) of patients that develop major LARS are likely to influence HRQoL [31,33]. In this study, patients with major LARS had significantly more complaints of embarrassment than patients with a stoma, which can be an important issue to discuss with a patient when a high risk of major LARS is anticipated.…”
Section: Discussionsupporting
confidence: 64%
“…As stated, the decision between an anastomosis and a (temporary) stoma after sphincter-sparing rectal cancer surgery is motivated by the risk of adverse events (e.g., anastomotic leakage) and the expected functional outcomes [12,33,45]. However, since this decision is usually not a straightforward one, caused by the lack of a clinically "best choice," considering the risks of poor functional outcome makes this decision preference-sensitive and therefore particularly relevant for shared decision-making [34,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the LARS score was higher in patients who were not obese and had undergone LAR, which is in agreement with the results of other studies [9,11,14]. Since it has been shown that sphincter-preserving surgery, such as AR and LAR, has negative effects on anorectal function, resulting in LARS [19], our study confirmed that patients who underwent LAR would develop LARS more frequently than those who underwent AR [20].…”
Section: Discussionsupporting
confidence: 91%
“…To draw a better picture of functional complaints in Vietnamese patients, a multi-center study is required. Another weak point of this study is that the LARS score was not able to discriminate patients who had undergone radiotherapy, even though radiotherapy has been proven to have a strong relationship to LARS [20].…”
Section: Discussionmentioning
confidence: 76%
“…A low tumour significantly increased the incidence of LARS, which could result from the difficulty of low rectal tumour resection and high anastomotic tension, easily leading to intestinal isospasm and stenosis at the proximal end of anastomosis 5,43,47 . The lower the distance between the tumour and the anal margin, the lower the position of the postoperative anastomosis.…”
Section: Discussionmentioning
confidence: 99%